Shifting and stopping: fronto-striatal substrates, neurochemical modulation and clinical implications - Robbins, T.W (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2007)
The neuropsychological basis of attentional set-shifting, task-set switching and stop-signal inhibition is reviewed through comparative studies of humans and experimental animals. Using human functional neuroimaging, plus neuropsychological investigation of patients with frontal damage quantified by structural magnetic resonance imaging, and through parallels with effects of specific lesions of the prefrontal cortex (PFC) and striatum in rats and marmosets, it is possible to define both distinct and overlapping loci for tasks such as extra-dimensional shifting and reversal learning, stop-signal reaction time and task-set switching. Notably, most of the paradigms implicate a locus in the right PFC, specifically the right inferior frontal gyrus, possibly associated with processes of response inhibition. The neurochemical modulation of fronto-striatal circuitry in parallel with effects on task performance has been investigated using specific neuropharmacological agents in animals and by human psychopharmacological investigations, sometimes in conjunction with functional imaging. Evidence is provided for double dissociations of effects of manipulations of prefrontal cortical catecholamine and indoleamine (5-HT) systems that have considerable implications in the treatment of disorders such as Parkinson's disease, attention deficit/hyperactivity disorder and depression, as well as in theoretical notions of how 'fronto-executive' functions are subject to state-dependent influences, probably related to stress, arousal and motivation.